الوصف في رواية الخيال العلمي رواية أحزان السندباد(+) أنموذجاً - الديوب سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يعدّ الوصف مدخلاً مناسباً لدراسة هذه الرواية؛ بسبب كثافة حضوره فيها. لذا يهدف هذا البحث إلى دراسة البعد الحَدَثي السردي في الوصف، وخصوصيات الوصف الفنية والدلالية، ووظائفه، وقدرته على مشاكلة الفنون الأخرى كالرسم، وارتباطه برؤية الروائي ورؤياه. والوصف في هذه الرواية وصفٌ ضمن نص سرديّ قائم على الخيال المرتبط بالعلم. ولرواية الخيال العلمي ميزة غير موجودة في سائر الروايات، تتمثل في كونها تحلِّق في أجواء الخيال المرتبطة بالعلم. Description can be regarded as an appropriate, beginning to study this novel because of its abundance; therefore, this paper seeks to explore the narrative action diminution on description, and the artistic and semantic characteristics of description, and description’s similarity to other arts like painting and its functions, the relation of description to the novelist’s vision and its own. Description in this novel is located within a narrative text, dependent upon science fiction, because this class of novel has a peculiar property unavailable in other novels, because it soars in the space of imagination related to science.